Evaluation of PALM - COEIN classification and management of abnormal uterine bleeding in peri-menopausal age group - Asudani, Nitya P.; Yadava, Pushpa A.; Vyas, Rupa C.; Jani, Shashwat K.; Rawal, Naisargee G.; Dangar, Kashmira V.; Patel, Heny J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) is a prevalent condition affecting a significant portion of women, particularly in the perimenopausal age group. The FIGO PALM-COEIN classification system, introduced in 2011, categorizes AUB based on its etiology and is a useful tool in diagnosing and managing AUB. The aim of the study was to evaluate the clinical and histopathological outcomes of AUB diagnoses in women based on this classification. Methods: A 6-month retrospective study was conducted in a tertiary care teaching hospital in western India, including 80 perimenopausal women, presenting with AUB between July and December 2024. Patients were assessed using clinical history, physical examination, and imaging. Additional diagnostic modalities like hysteroscopy and MRI were employed when necessary. Treatment outcomes were analyzed, focusing on medical and surgical interventions. Results: The majority of patients were in the 40-45 years age group (60%), with heavy menstrual bleeding (77.50%) being the most common bleeding pattern. Ultrasonography identified leiomyoma (38.75%) and adenomyosis (28.75%) as the most frequent causes. Histopathological examination of hysterectomy specimens revealed leiomyoma (45.58%), adenomyosis (30.90%), and endometrial hyperplasia (14.70%). Hysterectomy was the most common final treatment modality (85%). Conclusions: The PALM-COEIN classification system is a valuable, efficient tool for diagnosing AUB, facilitating targeted treatment strategies. Transvaginal ultrasonography remains the first-line imaging modality, but histopathological examination of all surgical specimens is essential to ensure comprehensive diagnosis and optimal management. Medical hormonal therapy is effective in most cases, but surgical options, including hysterectomy, remain crucial for definitive treatment.